Find the derivative of:

y=(x^2)(e^x) - 2x(e^x) + 2(e^x)

Thanks!

Printable View

- April 17th 2007, 07:45 PMcupcakelova87Derivative Problem
Find the derivative of:

y=(x^2)(e^x) - 2x(e^x) + 2(e^x)

Thanks! - April 17th 2007, 07:50 PMluckyc1423
x^2 * e^x

- April 17th 2007, 07:50 PMJhevon
y = (x^2)(e^x) - 2x(e^x) + 2(e^x)

=> y = (e^x)(x^2 - 2x + 2) .................................we need the product rule for this, hope you remember it

=> y' = (e^x)(x^2 - 2x + 2) + (e^x)(2x - 2) ...........now simplify

=> y' = (e^x)(x^2 - 2x + 2 + 2x - 2)

=> y' = (e^x)(x^2) - April 17th 2007, 07:51 PMecMathGeek
- April 17th 2007, 07:59 PMluckyc1423
lol, sorry...everyone does such a great job at helping me on here so I jumped at the chance when I knew the answer

- April 17th 2007, 08:12 PMcupcakelova87
Thanks to all :)